The Cognitive Load and its relation to Cognitive Holding Power among Umm Al-Qura University female students - Al-Otaibi, Atheer Khalid; Al-Harbi, Nawar Muhammad (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the relation between the Cognitive Load and the Cognitive Holding Power; to identify the types of the Cognitive Load and the orders of the Cognitive Holding Power among Umm Al-Qura University female students; and the possibility of predicting the Cognitive Load through the Cognitive Holding Power. The study sample consisted of (532) undergraduate female students in the scientific and humanitarian disciplines, who were chosen using the stratified random method. Dr. Alfeel’s Cognitive Load Scale for adults (2015) and Stevenson and Evans’ Cognitive Holding Power questionnaire – codified by Al-Khafagi (2018) were applied to the sample. The descriptive approach was used. The study findings showed a direct, statistically significant correlation between the Intrinsic Cognitive Load, the Germane Cognitive Load, and the Cognitive Holding Power. There is also a statistically significant inverse correlation between the Extraneous Cognitive Load and the Cognitive Holding Power. Umm Al-Qura University female students have an average level of Cognitive Load and Cognitive Holding Power. The most prominent types of their Cognitive Load were the Germane Cognitive Load. The most prominent orders of the Cognitive Holding Power were represented in the Second Order. The study recommended increasing interest in developing cognitive structures and improving learning environments so that they become supportive of the Second Order Cognitive Holding Power and away from the pressures that lead to the Cognitive Load.